COVID-19 Impact Monitoring the the Household Level : Burkina Faso, Bulletin No. 2 - World Bank (World Bank, Washington, DC, 2021)
This note presents the results of the second round of a nationally representative telephone survey (HFPS). Data collection took place between July 20 and August 14, 2020. The 1,968 households that were successfully interviewed during the first round were called and 1,860 (94.5 percent of the 1,968) were interviewed with success in the second round. In addition, 242 additional household were sampled in the rural strata during the second round, in order to increase representativeness in this area. Of the 242 households in the sample, 177 households (73.14 percent of 242 attempts) were contacted and interviewed successfully. The entire sample of the second round includes 2,037 households. For this second round, the questionnaire includes two key modules that were already administered in the first pass, namely, access to food and basic services (health, education, etc.), and employment and income. Four new modules are added, covering the following themes : food security, shocks, fragility, conflict and violence.